Controlling the stability of chocolates through the incorporation of soft and hard StOSt‐rich fats. Issue 11 (20th July 2015) - Tran, Phuong Diem; Van de Walle, Davy; Hinneh, Michael; Delbaere, Claudia; De Clercq, Nathalie; Tran, Dung Nhan; Dewettinck, Koen
Abstract : The presented study investigates the functionality of hard and soft StOSt‐rich fats in plain and hazelnut‐based filled dark chocolates. Blends of cocoa butter (CB) with different StOSt‐rich fats, namely Vietnamese mango fat (VMF), Indian mango fat (IMF), its stearin (IMFst) and olein fraction (IMFol) were selected for application in these chocolate products based on their phase and crystallisation behaviour. It was shown that a fat phase formulation with CB/VMF 70/30 and CB/IMFst 70/30 increased the heat resistance of dark chocolate and maintained similar chocolate quality attributes (colour, hardness, melting and flow properties) compared to the CB reference. Furthermore, these fat blends increased the fat bloom stability following oil migration, as shown by visual assessment by a trained panel, cryo‐SEM imaging and oil migration monitoring by HPLC‐ELSD. In addition, the fat blend CB/IMFol 90/10, suitable for chocolate applications under non‐tropical conditions, was shown to retard oil migration fat bloom as well. Distinct mechanisms for the observed phenomena were proposed. Furthermore, the different steps of fat bloom development, starting from the appearance of oil blisters to the presence of crystals (∼30 μm) on the chocolate surface were captured using cryo‐SEM. Practical applications: (i) heat resistant chocolate with increased fat bloom stability was developed; (ii) fat boom development in filled chocolates can be delayed tuning the TAG composition and (iii) a cost‐effective source of mango fat was provided with several technical applications for the tropics. By tuning the TAG composition, several compatible fat blends of cocoa butter (CB) and mango fats (MF) are obtained. In comparison to the CB reference chocolate, the fat phase formulation with hard StOSt‐rich fats (CB/VMF 70/30 and CB/IMFst 70/30) increases the heat resistance of dark chocolate likely without inducing a waxy mouthfeel. Furthermore, both hard and soft StOSt‐rich fats increase the stability towards oil migration fat bloom, as observed by cryo‐SEM imaging. Explanations are proposed based on TAG composition. Abstract : By tuning the TAG composition, several compatible fat blends of cocoa butter (CB) and mango fats (MF) are obtained. In comparison to the CB reference chocolate, the fat phase formulation with hard StOSt‐rich fats (CB/VMF 70/30 and CB/IMFst 70/30) increases the heat resistance of dark chocolate likely without inducing a waxy mouthfeel. Furthermore, both hard and soft StOSt‐rich fats increase the stability towards oil migration fat bloom, as observed by cryo‐SEM imaging. Explanations are proposed based on TAG composition.